Implementation of Environmentally Based Citizenship Education in Increasing Waste Management Awareness in Students - Bherrio Dwi Saputra; Wachid Pratomo; Ficky Adi Kurniawan (Tecno Scientifica Publishing, 2026)
Waste management was a growing environmental challenge that required the development of public awareness from an early age. Schools played a strategic role in fostering such awareness through the learning process, including Civics Education (PKn), which integrated environmental values. This study aimed to analyze the implementation of environment-based civics education in increasing students’ waste management awareness. A systematic literature review was employed by examining relevant scientific articles on civics education, ecological citizenship, environmental education, and waste management published between 2015 and 2025. Data were collected from Google Scholar, ScienceDirect, SpringerLink, and Garuda, and were analyzed using content analysis techniques to identify key concepts, learning approaches, and major findings. The review indicated that environment-based civics education improved students’ waste management awareness by strengthening social responsibility, promoting ecological citizenship, and encouraging practice-based learning such as 5R-based activities (Reduce, Reuse, Recycle, Replace, and Replant). However, its implementation remained constrained by limited curriculum integration, insufficient school facilities, and inadequate teacher competence in integrating environmental values into learning. Therefore, strengthening the integration of environmental education into civics education was essential to develop students’ ecological awareness more effectively.